Research on the Allocation of 3D Printing Emergency Supplies in Public Health Emergencies - He, Jianjia; Liu, Gang; Mai, Thi Hoai Thuong; Li, Ting Ting (Frontiers in Public Health, 2021)
Significant public health emergencies greatly impact the global supply chain system of production and cause severe shortages in personal protective and medical emergency supplies. Thus, rapid manufacturing, scattered distribution, high design degrees of freedom, and the advantages of the low threshold of 3D printing can play important roles in the production of emergency supplies. In order to better realize the efficient distribution of 3D printing emergency supplies, this paper studies the relationship between the supply and demand of 3D printing equipment and emergency supplies produced by 3D printing technology after public health emergencies. First, we fully consider the heterogeneity of user orders, 3D printing equipment resources, and the characteristics of diverse production objectives in the context of the emergent public health environment. The multi-objective optimization model for the production of 3D printing emergency supplies, which was evaluated by multiple manufacturers and in multiple disaster sites, can maximize the time and cost benefits of the 3D printing of emergency supplies. Then, an improved nondominated sorting genetic algorithm (NSGA-Ⅱ) to solve the multi-objective optimization model is developed and compared with the traditional NSGA-Ⅱ algorithm analysis. It contains more than one solution in the Pareto optimal solution set. Finally, the effectiveness of 3D printing is verified by numerical simulation, and it is found that it can solve the matching problem of supply and demand of 3D printing emergency supplies in public health emergencies.